The Ukraine-Russia Conflict: A Comprehensive Analysis of Causes, Consequences, and International Implications - Demyan Fyodor (Global Writing Academica Researching & Publishing, 2023)
This journal article provides a comprehensive analysis of the ongoing conflict between Ukraine and Russia. The article examines the historical background, underlying causes, geopolitical factors, and consequences of the conflict. Additionally, it explores the international implications of the conflict and the efforts made towards resolving the crisis. By examining various perspectives and drawing on scholarly research and primary sources, this article aims to deepen the understanding of the Ukraine-Russia conflict and contribute to the discourse on conflict resolution and international relations.